Deep Flux-Weakening Strategy with MTPV for High-Speed IPMSM for Vehicle Application. Issue 28 (2018) - Fadel, Maurice; Sepulchre, Leopold; Pietrzak-David, Maria
Abstract: High speed Interior Permanent Magnet Synchronous Motors (IPMSM) are used in embedded applications for their high-power density and efficiency. Because of the voltage limit of the supply, operating at such speed requires to do flux-weakening by adding negative Id current. The optimal current reference trajectory in the d-q frame for a torque reference that minimized the current norm while respecting the current and voltage limits, is calculated. When all the magnet contribution to the airgap is compensated, the trajectory that maximizes the power output is the Maximum Torque Per Volt (MTPV) trajectory and this one doesn't correspond to maximum current operation. In this paper is proposed a new flux-weakening algorithm that includes the MTPV trajectory without algorithm switching. A second variable current limit is added that corresponds to the current norm required by the analytical MTPV solution. A description of the existing deep-flux-weakening techniques is carried out. The efficiency of the proposed method is validated and compared to existing techniques throw experiments on a small scaled motor. The results show an increase of the torque (and power) and a reduction of the losses when operating at very high speed. Finally, an over speed of 9, 23 is reached.